An Interventional Quandary—Clipping vs Coiling vs STA-MCA Bypass in a Ruptured Basilar Tip Aneurysm with Bilateral ICA Stenosis: A Rare Case Report and a Comprehensive Review - Rahul Sharma; Anand Katkar; Ashok Bhanage; Chintan Popat (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Our primary goal is to report a detailed case outlining the clinical and radiological characteristics of an extremely rare condition: bilateral internal carotid artery (ICA) stenosis with ruptured basilar tip aneurysm, and bilateral posterior cerebral arteries (PCAs) arising from the sac, treatment options, as well as its outcome. We searched the PUBMED database from 1980 to 2023 for similar case reports. Among seven similar cases found, two were conservatively managed, focusing on reducing intracranial pressure (ICP). One out of two survived, while one ended in fatality. In the other five cases, interventions (endovascular in four/STA-MCA (superficial temporal artery–middle cerebral artery) bypass in one) were pursued, resulting in significant recovery and discharge. Dealing with such complex cases with uncommon pathoanatomy poses treatment challenges due to their hemodynamics and the risk of collateral flow cessation despite multiple available treatment options.